Responding to the Call: Information Systems Graduate Preparation and Job Needs - Simon, DeShea (Current Research in Language, Literature and Education Vol. 3, 2022)
This study examined the perspectives on academic preparation and job skill needs of Information Systems program graduates from an Eastern state in the US. A historical review of the literature surrounding information systems skill requirements was conducted for this study, to provide an understanding of the changes in information systems over the past several decades. This historical look at the literature placed into perspective the fact that the field changes rapidly, causing the need for the information systems professional to also continuously change. The study employed a non- experimental, research design to allow a descriptive interpretation of the views of recent IS graduates. The results of the study revealed that a consensus exists regarding the perceptions of the skills needed for the information systems worker. However, graduates are concerned about how these skills are being delivered to develop competent information systems professionals for the work force.